Towards a Husserlian Foundation of Aesthetics On Imagination, Phantasy & Image Consciousness in the 1904/1905 Lessons - Katz Russo, Azul Tamina (2016)
While it is true that Husserl did not write systematically about aesthetics, it is not only possible and legitimate but also necessary to inquire how a Husserlian aesthetic consciousness could be understood. A closer consideration of the aesthetics that can be gleaned from the passages in which Husserl explicitly refers to artistic experiences shows a limitation of the aesthetic field to figurative art. To widen and enrich the aesthetic field beyond the experiences that such an aesthetics would account for, a shift of perspective is required. But to allow this change without leaving Husserl’s phenomenology, I consider in this article the outcome of analyzing this field of experiences from phantasy’s perspective instead of that of image consciousness.